NESTOR facility injection conception - Gladkikh, P.; Karnaukhov, I.; Mytsykov, A.; Skyrda, V.; Zelinsky, A. (Вопросы атомной науки и техники, 2011)
During the last years X-ray generator NESTOR is under construction in NSC KIPT. According to the project, 60 MeV electrons are injected in the storage ring and further can be accelerated up to the maximal energy 225 MeV . Due to compact design of the ring, injection trajectory of the beam passes through fringe field of NESTOR bending magnet. It brings additional difficulties of injection system design. In the paper the results of NESTOR facility injection system are presented. The results show that designed system provides matching of injected beam parameters with the storage ring acceptance and is stable to element alignment errors.